Respuesta :
Answer:
The answer is 4(3x² + 1)(x - 5).
Step-by-step explanation:
First, you have to take out all the common ratios :
12x³ - 60x² + 4x - 20
= 4(3x³ - 15x² + x - 5)
Next, you have to factorize the inner brackets :
3x³ - 15x² + x - 5
= 3x²(x - 5) + (x - 5)
= (3x² + 1)(x - 5)
Answer:
4(3x² + 1)(x - 5)
Step-by-step explanation:
Given
12x³ - 60x² + 4x - 20 ← factor out 4 from each term
= 4(3x³ - 15x² + x - 5)
Factor the first/second and third/fourth terms inside the parenthesis
= 4[ 3x²(x - 5) + 1(x - 5) ] ← factor out (x - 5) from each term
= 4(3x² + 1)(x - 5)